RESEARCHES IN EDUCATION AND CONTINUOUS FORMATION: POSSIBILITIES IN THE PROFESSIONAL DEVELOPMENT OF PHYSICAL EDUCATION TEACHERS (Fiep Bulletin - online, 2015)
The teachers are professionals of education, whose preparation presents two moments, the initial and continuous phase, that are dimensions of the same process, because, they present an organic continuity between each other. One of the ways for continued formation of teachers is the participation in researches in the educational area. The researches in education have been developed in several epistemological focuses and with their consequent methodological approach. The research-action is constituent of the methodological procedures of the dialectic critical focus. The continuous formation of teachers concept needs to be rethought and in this purpose we have been evidencing that the research-action, at the same time in that it enables the construction and elaboration of new studies and knowledge, it can also be considered as moment of continuous professional preparation. To do so, a research-action based on a cooperative and collective action was idealized, which main objective is to establish a reflexive practice with researches in the teaching post, having, as consequence, professional autonomy. The study is being developed, through weekly meetings, although the space of development of the same has been demonstrating to be more extensive. This way, the intentions are to outset from real needs, because the contextualization process it is important when seeking awareness of what is knowledge of knowledge, opening possibilities for critical positioning and reconstruction of ontological and epistemological conceptions. Some initial indicators demonstrate positive results, that are: a) improvement of the quality of the interactions; b) teachers identifying problems in their actions and proposing solutions; c) teachers' intellectual production under the form of production of texts, implementation of courses and organization of events; d) elaboration of research projects by teachers, individually or in group, to be developed in their classes.
Keywords: Research in education; continuous formation; physical education.